2006
DOI: 10.2169/internalmedicine.45.1532
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and the Incidence of Coronary Artery Disease in Young Middleaged Japanese Men: Results from a 10Year Cohort Study

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Although elevated BP was strongly associated with mortality from hemorrhagic stroke, 20,21 elevated glucose level was associated with mortality from coronary heart disease 22,23 in both sexes. In men, reduced HDL 24,25 and being overweight 26 were also associated with mortality from coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although elevated BP was strongly associated with mortality from hemorrhagic stroke, 20,21 elevated glucose level was associated with mortality from coronary heart disease 22,23 in both sexes. In men, reduced HDL 24,25 and being overweight 26 were also associated with mortality from coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the NIPPON DATA90, the HDL-C level was found to be significantly inversely correlated with overall mortality and stroke mortality during the 9.6-year observation period 36) . Community and worksite-based cohort studies have shown that an HDL-C level 40 mg/dL is associated with an increased risk of CAD 11, [37][38][39] . In the J-LIT, a cohort study, simvastatin-treated primary prevention patients 12) and secondary prevention patients 13) with an HDL-C level 40 mg/dL were found to have a intervention significantly decreases the incidence of CAD.…”
Section: Hypo-hdl Cholesterolemiamentioning
confidence: 99%
“…The incidence of coronary artery diseases is much lower in Japan than in western countries, 9,10 but the number of individuals transported is affected not only by disease incidence but also by residents' decisions to call or not call an ambulance. Thus, it is reasonable to believe that the decrease in ambulance calls by individuals diagnosed as having such diseases was due to the campaign.…”
Section: Discussionmentioning
confidence: 99%